The relationship between patriotism and regional identification: a cross-country analysis - Peter Dirksmeier (The Annals of Regional Science, 2022)
Patriotism—as an ambivalent attitude towards the nation—has less exclusionary characteristics than nationalism and regional identification, because it does not require comparisons and hierarchies. What is less clear, however, is how to explain the positive evaluation of patriotism in the wider population. The article analyses the positive relationship of patriotism with nationalism and regional identification in 29 national and 421 regional contexts. The paper clearly shows that different factors explain the positive evaluation of patriotism and the mind-set of patriotism itself. While a nationalist attitude and regional identification at the individual level are strongly associated with a positive evaluation of patriotism and patriotism itself, institutionalised forms of regional autonomy are shown to be insignificant for the evaluation of patriotism and ambivalent for patriotism itself at the context level. The article concludes by discussing these results in the context of a Janus-faced nature of regional identification that can contribute to an inclusive society as much as to a nationalist-chauvinist attitude and which has so far been overlooked in regional science.
Keywords: Z00; Z19; 500